Activation of Peroxisome Proliferator-Activated Receptor γ by Rosiglitazone Inhibits Lipopolysaccharide-Induced Release of High Mobility Group Box 1 - Jung Seok Hwang; Eun Sil Kang; Sun Ah Ham; Taesik Yoo; Hanna Lee; Kyung Shin Paek; Chankyu Park; Jin-Hoi Kim; Dae-Seog Lim; Han Geuk Seo (Mediators of Inflammation, 2012)
Peroxisome proliferator-activated receptors (PPARs) are shown to modulate the pathological status of sepsis by regulating the release of high mobility group box 1 (HMGB1), a well-known late proinflammatory mediator of sepsis. Ligand-activated PPARs markedly inhibited lipopolysaccharide- (LPS) induced release of HMGB1 in RAW 264.7 cells. Among the ligands of PPAR, the effect of rosiglitazone, a specific ligand for PPARγ, was superior in the inhibition of HMGB1 release induced by LPS. This effect was observed in cells that received rosiglitazone before LPS or after LPS treatment, indicating that rosiglitazone is effective in both treatment and prevention. Ablation of PPARγ with small interfering RNA or GW9662-mediated inhibition of PPARγ abolished the effect of rosiglitazone on HMGB1 release. Furthermore, the overexpression of PPARγ markedly potentiated the inhibitory effect of rosiglitazone on HMGB1 release. In addition, rosiglitazone inhibited LPS-induced expression of Toll-like receptor 4 signal molecules, suggesting a possible mechanism by which rosiglitazone modulates HMGB1 release. Notably, the administration of rosiglitazone to mice improved survival rates in an LPS-induced animal model of endotoxemia, where reduced levels of circulating HMGB1 were demonstrated. Taken together, these results suggest that PPARs play an important role in the cellular response to inflammation by inhibiting HMGB1 release.